2021
DOI: 10.3390/ijms22189804
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-Directed Tumor Microenvironment Modulation in Cancer Immunotherapy

Abstract: Chemokines are a large family of small chemotactic cytokines that coordinates immune cell trafficking. In cancer, they have a pivotal role in the migration pattern of immune cells into the tumor, thereby shaping the tumor microenvironment immune profile, often towards a pro-tumorigenic state. Furthermore, chemokines can directly target non-immune cells in the tumor microenvironment, including cancer, stromal and vascular endothelial cells. As such, chemokines participate in several cancer development processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 186 publications
(219 reference statements)
0
58
0
Order By: Relevance
“…Also, HHLA2 expression was found to be favorably associated to a number of chemokines, including CCL2, CCL20, and CXCL2. It was reported that such chemokines secreted by tumor cells and the microenvironment contribute to the recruitment of immunosuppressive cells into the tumor, such as MDSC, Treg, and TAM ( 38 40 ). Furthermore, these immunosuppressive cells can suppress CD8+ T-cell function, and interact with other immune regulatory cells which leads to exhaustion of cytotoxic T cells in tumor tissues ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, HHLA2 expression was found to be favorably associated to a number of chemokines, including CCL2, CCL20, and CXCL2. It was reported that such chemokines secreted by tumor cells and the microenvironment contribute to the recruitment of immunosuppressive cells into the tumor, such as MDSC, Treg, and TAM ( 38 40 ). Furthermore, these immunosuppressive cells can suppress CD8+ T-cell function, and interact with other immune regulatory cells which leads to exhaustion of cytotoxic T cells in tumor tissues ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Progression of HCC is not solely determined by biological features of cancer cells, such as their proliferation rate, but is also restricted and modulated by a TME composed of a network of immune and stroma cells. Of note, the chemokine CXCL10 has already been implicated in acute and chronic fibrosis as well as carcinogenesis [ 4 , 18 , 19 , 20 ]. Next, we set out to characterize the relevance of CXCL10 for the fibrotic non-tumorigenic microenvironment and the tumor stroma composition during hepatic carcinogenesis using HCC- bearing WT and Cxcl10 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, chemokines have been used as important therapeutic targets for cancer. Mogamulizumab (an anti-CCR4 antibody) and Plerixafor/AMD3100 (a CXCR4 antagonist) have been approved for the treatment of hematologic malignancies and being in clinical trials ( Bule et al, 2021 ). In addition, Wsetermann et al used CCL19-conjugated DNA vaccine for tumor control and showed that the combination of the two significantly inhibited tumor growth and prolonged the antitumor effect of the vaccine ( Westermann et al, 2007 ).…”
Section: Chemokines In Clinical Research and Applicationsmentioning
confidence: 99%